REASONS OF DOMESTIC VIOLENCE - Urazaliev Murod Koraevich (PT. Antis International Publisher, 2025)
Objective: This article aims to explore the causes and negative aspects of domestic violence, emphasizing its psychological mechanisms and examining methods of prevention. It investigates the theories surrounding aggression and violence in human behavior. Method: The study utilizes psychological theories, including Sigmund Freud's concept of